Developing E-worksheet-based TPACK model for Junior High School Students in English Language Learning Context - Meldia, Putri; Melani, Melyann; Kardena, Absharini; Roza, Veni (Script Journal: Journal of Linguistics and English Teaching, 2024)
Background:The goal of this study is at developing an E-Worksheet based on TPACK Model by using Adobe Animate CC and AI Voice. This research was conducted to overcome the students’ problem, the teacher’s problem, and instructional problem that occurred in Language classroom. Methodology:This study is a research and development project that used of the 4D development methodology. The four steps of this model's development are defining, designing, developing, and distributing. Observations, tests, interviews, and questionnaires are examples of research instruments. The e-worksheet was validated by 5 validators, including 2 material and language expert lecturers and 3 media expert lecturers. Findings:The percent formula is used to determine its practicality. The electronic worksheet is classified as very valid with the level of 84.2 % in material or content of product and very valid with the level of 85.9% in media of product. The result of the practicality of the electronic words indicated that the total mean score for all the items in the questioner was 4.5 with a percentage of 90 falling into the category of very practical. The results of the effectiveness test were obtained with a value of 0.81 in the high category. Conclusion:Based on the results of the study it can be concluded that developing an E-Worksheet in Describing words material based on the TPACK Model by using Adobe Animate CC and AI Voice for seventh grade students of Junior Islamic High School is valid, practical, and effective. Originality:The use of TPACK as a resource for creating teaching materials is quite effective